Rodolfo Kusch's ‘Estar’ as Seen from the Systemic Perspective of Humberto Maturana as a way of ‘corazonar’ Coexistence - Holas, Sergio (The Australian Journal of Indigenous Education, 2017)
In this paper, I further develop Rodolfo Kusch's concept of ‘negation’. I argue that it is an affirmative tool that enables us to sense and feel the other sides or domains of what we call reality and allows us to approach a plateau negated as a horizon of possibilities for conviviality and coexistence. Kusch's concept of negation brings forth an image of the emotions as being intimately interconnected to the values and ethos that form the basis of our behaviours. This paper also argues that Kush's concept of negation must be considered together with Kusch's development of ‘estar’ as a philosophical concept which underpins ‘América profunda’ ways of being in the world (or the multiverse). Finally, I propose that this ‘estar’ requires a ‘corazonar’ of our ways of bringing forth ourselves and our territories to life.